American scoundrel the life of the notorious Civil War General Dan Sickles - Keneally, Thomas (Anchor Books, 2003)
Hero, adulterer, bon vivant, murderer and rogue, Dan Sickles led the kind of existence that was indeed stranger than fiction. Throughout his life he exhibited the kind of exuberant charm and lack of scruple that wins friends, seduces women, and gets people killed. In American Scoundrel Thomas Keneally, the acclaimed author of Schindler's List, creates a biography that is as lively and engrossing as its subject. Dan Sickles was a member of Congress, led a controversial charge at Gettysburg, and had an affair with the deposed Queen of Spain-among many other women. But the most startling of his many exploits was his murder of Philip Barton Key (son of Francis Scott Key), the lover of his long-suffering and neglected wife, Teresa. The affair, the crime, and the trial contained all the ingredients of melodrama needed to ensure that it was the scandal of the age. At the trial's end, Sickles was acquitted and hardly chastened. His life, in which outrage and accomplishment had equal force, is a compelling American tale, told with the skill of a master narrative.